“We are three lengths away from the final stretch”: notes on Polyphony of a Race by Karo Castro (2024) - Campillay Covarrubias, Catherina (Nomadías, 2025)
Like many other animal species, we could trace the history of the horse in parallel to the history—which we generally know better—of humans. Rather, the latter would be impossible to understand without their presence, our bond and their domestication, the fascination they have provoked over the centuries. From their appearance in cave paintings up to 32 thousand years ago - those figures of time almost impossible to understand -, through their importance in foundational texts such as The Iliad, reaching a present in which they have been replaced as the most reliable and fastest method of transportation, a place they had for centuries, along with being important forces in war and agriculture.